Optimization of Financial Technology as an Opportunity for Development of Islamic Microfinance Institutions - Ramadhani Irma Tripalupi; Lina Yulianti; Didah Durrotun Naafisah (Universitas Dharma Wacana, 2022)
This study discusses the strategy of developing Islamic microfinance institutions facing the era of financial technology in West Java. The study examines internal strategy factors in the development strategy of Islamic Microfinance Institutions (LKMS), external strategy factors, and the formulation and alternative development strategies. In conclusion, the internal strategic factors include generally good financial performance, increasing trend of public deposits, suitable financing and supporting the strengthening of Micro, Small & Medium Enterprises (MSMEs), risk management implemented effectively and gradually, and digital-based services (savings, financing proposals) & payment), education and assistance, easy access, competency development of human resources and members, development of information technology organization tools, innovation in strengthening competitiveness (digitalization of services, development of human resources in the field of information technology), relations, collaboration with institutions others (sharia fintech/marketplace platforms, etc.), and digital marketing strategies. The external strategic factors include: relatively good investment realization, government support, fintech-based services (zakat and waqf), the performance of the national and Islamic finance industry is quite good, global and national economic growth is not conducive, and the market share of the Islamic finance industry is still low, other financial institutions in providing services to MSMEs or digital-based services, and household consumption activities have decreased. The formulation and alternative of SWOT analysis with EFAS and IFAS approach resulted in a weighted EFAS of 3.03 and a weighted IFAS of 2.95. BOS results in: eliminating barriers to inclusion, reducing investment of less productive funds, increasing assistance and excellent service, and creating fintech service innovations in the form of a crowdfunding platform.